Anise—Pimpinella anisum L. - James M. Stephens (EDIS)
This document details the cultivation and uses of anise (Pimpinella anisum L.), an annual herb known for its seeds and oil used in flavoring, medicines, and perfumes. The document covers the plant's growth requirements, harvesting methods, and potential for production in various regions, including Florida. It emphasizes the importance of soil quality, climate conditions, and proper harvesting techniques to ensure high-quality yield. Original publication date April 1997.